On the Development of a Ring Type Mechanical Force Transducer: Experimental Characterization and Finite Element Study - van Stratan, Gavin Scott Manggai (Curtin University, 2019)
This research focuses on the design of a ring type mechanical force transducer by varying the cross-sectional shape. Shape optimization codes produced minimum ring thickness between 45-60° with maximum thickness at point of load application. All optimization codes were found to have lowered stress levels. The modified ring design was found to have favourable comparisons with the other conventional rings. A double ring design has lower stress levels compared to the modified ring design.